Evaluasi atas Sistem Pembelian dalam Kaitannya dengan Pengendalian Intern Studi Kasus pada PT. Inti Sari Prima - Iriyadi, Iriyadi; Rianna, Rianna (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2009)
The objective of this research is to find out purchasing accounting system and internal control implementation of company and to find out purchasing system result in accordance with internal control of company. From the result of this research, it can be found out that purchasing system and procedure have been suffice enough, but internal control at PT Intisari Prima still has a lot of shortages. However, the company has endeavored by implementing true purchasing accounting system and procedure by separating three main functions as follows: operational function (purchasing division), storing function (storehouse division), and accounting function (registration section). It can not be permitted that just one function brings about transaction from the beginning to the end in maintaining the companyâs assets. Keyword : Purchasing Accounting System